2012
DOI: 10.1074/jbc.m111.319566
|View full text |Cite
|
Sign up to set email alerts
|

Sublytic C5b-9 Complexes Induce Apoptosis of Glomerular Mesangial Cells in Rats with Thy-1 Nephritis through Role of Interferon Regulatory Factor-1-dependent Caspase 8 Activation

Abstract: Background:The mechanism of sublytic C5b-9-mediated glomerular mesangial cell (GMC) apoptosis in rat Thy-1 nephritis remains unclear. Results: GMC apoptosis was induced by sublytic C5b-9 via the interferon regulatory factor-1 (IRF-1)/caspase 8-dependent pathway, in which IRF-1 up-regulated caspase 8 activity. Conclusion: Sublytic C5b-9 could promote GMC apoptosis in Thy-1 nephritis through IRF-1-activation of caspase 8. Significance: IRF-1 might provide a potential target for human mesangioproliferative glomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 50 publications
(64 reference statements)
0
59
1
Order By: Relevance
“…Our study showed that plasma concentration of C5b-9 significantly lower in CAL. Maybe most C5b-9 was primarily deposits in the glomerulus and lead lower blood concentration (26). There may be an association with other increased complement regulatory proteins (CD35, CR1, CR2, and Crry) in vivo, which regulate immune status and inhibit complex formation, with C5b-9 in dynamic balance, but the specific biological mechanism needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that plasma concentration of C5b-9 significantly lower in CAL. Maybe most C5b-9 was primarily deposits in the glomerulus and lead lower blood concentration (26). There may be an association with other increased complement regulatory proteins (CD35, CR1, CR2, and Crry) in vivo, which regulate immune status and inhibit complex formation, with C5b-9 in dynamic balance, but the specific biological mechanism needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of anti-Thy1 glomerulonephritis as an experimental model for mesangial proliferative glomerulonephritis was reported by some investigators [30,31] . Administration of anti-Thy1 to rats leads to proliferative glomerulonephritis, which is characterized by complement dependent injury of mesangial cells, followed by mesangial proliferation.…”
Section: Discussionmentioning
confidence: 81%
“…Primer sequences for SRY gene (forward, 5'-CAT CGA AGG GTT AAA GTG CCA-3', reverse 5'-ATA GTG TGT AG-GTT GTT GTC C-3') were obtained from published sequences by Bruckner et al and amplified a product of 104 bp [15] . The PCR conditions were as follow: incubation at 94 °C for 4 min; 35 cycles of incubation at 94 °C for 50 seconds, 60 °C for 30 seconds, and 72 °C for 1 min; with a final incubation at 72 °C for 10 min. PCR products were separated using 2% agarose gel electrophoresis and stained with ethidium bromide.…”
Section: Pcr Detection Of Male-derived Mscsmentioning
confidence: 99%
“…Furthermore, sublytic C5b-9 deposition induces apoptosis by up-regulating the interferon regulatory factor-1 caspase 8/caspase 3 pathways, an event that leads ultimately to endothelial cell detachment and subsequent activation of the indirect clotting pathway via exposure of type IV collagen (20). Eculizumab would effectively block these MAC-mediated procoagulant events.…”
Section: Discussionmentioning
confidence: 99%
“…In renal transplant recipients, it has been used for the treatment of a variety of complement/ antibody-mediated microangiopathy syndromes including aHUS (24,25) and antibody-mediated rejection (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and in single case studies of patients with CAPS (13) and APS (27).…”
Section: Discussionmentioning
confidence: 99%